Pengaruh Penggunaan Handphone Berlebihan Terhadap Tingkat Percaya diri Pada Siswa-Siswi SMP Negeri 1 Delitua Kelas 9.6 - Ainul Mardiyah; Rani Hidayah Br Kaban; Mhd Hanif Al Fath; Sabila Yassarah Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the effect of excessive cellphone use on the level of self-confidence of 9th grade students. High cellphone use among adolescents is often associated with decreased social interaction, increased anxiety, and reduced self-confidence. The study used a quantitative approach with a two-variable questionnaire instrument, namely the intensity of cellphone use and the level of self-confidence. The results of the study showed that excessive cellphone use has a negative relationship with students' level of self-confidence. The higher the intensity of cellphone use, the lower the students' self-confidence.